Periprosthetic Osteolysis after Total Wrist Arthroplasty - Boeckstyns, Michel E. H.; Herzberg, Guillaume (Journal of Wrist Surgery, 2014)
Background and Literature Review Periprosthetic osteolysis (PPO) after second- or third-generation total wrist arthroplasty (TWA), with or without evident loosening of the implant components, has previously been reported in the literature, but rarely in a systematic way.Purpose The purpose of this study was to analyze the prevalence, location, and natural history of PPO following a TWA and to determine whether this was associated with prosthetic loosening.Patients and Methods We analyzed 44 consecutive cases in which a RE-MOTION TWA (Small Bone Innovations Inc., Morrisville, PA, USA) had been done. Results We found significant periprosthetic radiolucency (more than 2 mm in width) at the radial component side in 16 of the cases and at the carpal component side in 7. It developed gradually juxta-articularly around the prosthetic components regardless of the primary diagnosis, and seemed to stabilize in most patients after 1–3 years. In a small percentage of the patients, the periprosthetic area of bone resorption was markedly larger. In general, radiolucency was not related to evident loosening of the implant components, and only five carpal components and one radial had subsided or tilted.Conclusion Periprosthetic loosening is frequent following a TWA. In our series it was not necessarily associated with implant loosening and seemed to stabilize within 3 years. Close and continued observation is, however, recommended.Level of Evidence Therapeutic IV
Keywords: wrist; arthroplasty; osteolysis; radiolucency